An anatomical aspect on masseteric muscles in cattle rabies by real-time pcr - Atilla Yoldaş; Ramazan İlgün; Nevin Tuzcu; Akın Yığın; Erdal Özmen (Eurasian Journal of Veterinary Sciences)
Aim: In this case, the anatomical pathways on masticatory muscles of cattle infected rabies virüs have been determined by Real Time PCR (RT-PCR). Materials and Methods: A 1.5-year old male Brown Swiss cattle which was bitten in face by dog was used. The cattle was died 15 days post exposure to the dog rabies suspected. The areas where the tissue samples to taken. The origin, course and branches of the trigeminal nerve were exposed by standart dissection method. Rabies virus was investigated on 32 different parts of the cattle's head by means of TaqMan Probe-Based Real-Time PCR and FAT. Results: The rabies virus specific nucleic acid was detected in masseter muscles motor nerves; N. mandibularis branch of N. trigeminus, N. masticatorius, motor leaf of N. mandibularis, N. massetericus and Nn. temporalis profunda which are two extra branches of N. masticatorius, unilaterally ganglion trigeminale, and pons by Real Time-PCR. However, no rabies virus has been detected in the samples obtained from other different parts of the brain. Conclusion: Contrary to immunohistochemical methods, it is not possible to trace neuronal connections across synapses within the brain. RT-PCR method could be helpful to detect pathways of the neurotropic agents suspected cattle.